THE EFFECT OF UTILIZING ANIMATED VIDEO MEDIA ON SCIENCE LEARNING IN GRADE V OF SD NEGERI 1 GEGESIK KULON - Lala Qodrayani; Mimin Darmini; Nugraha Permana Putra (SOSIOEDUKASI, 2026)
Science learning in elementary schools often encounters low student comprehension due to the dominance of conventional teaching methods and the abstract nature of the concepts. This study aims to determine the effect of utilizing animated video media on science learning outcomes, specifically on the Solar System topic, for grade V students at SD Negeri 1 Gegesik Kulon. A quantitative approach with a quasi-experimental Nonequivalent Control Group Design was employed. The sample consisted of grade V students, divided into an experimental group of 30 students and a control group of 30 students, selected via saturated sampling. Data were collected through pre-tests and post-tests, and subsequently analyzed using the Independent Sample T-Test. The results demonstrated a significant increase in the experimental group, with the mean score rising from 31.33 on the pre-test to 91.67 on the post-test. In contrast, the control group's mean score decreased from 28.67 on the pre-test to 17.17 on the post-test. Statistical analysis yielded a t-count of 4.267, which is greater than the t-table of 2.001, and a significance value (Sig. 2-tailed) of 0.000 < 0.05. These findings indicate that the utilization of animated video media has a highly significant and positive effect on improving students' science learning outcomes. The media effectively visualizes abstract concepts, accommodating both visual and auditory learning needs, thereby increasing student engagement and understanding in science education.